PENGEMBANGAN TOPIK DI DALAM CET MENGGUNAKAN BAHASA INGGRIS - Hamzah, Hamzah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
The study is aimed at investigating the way the participants develop the topics in chatting, synchronous computer mediated interaction.Â  Data were obtained from lobbies of several chatrooms at yahoo.com. The findings revealed that the topic being developed by the participants did not necessarily in line with the topic prescribed by administrator of each room. The newly joined participants marked the introduction of the topic using metacomment while the current participants introduce the topic apruptly. The closing of the topic tend to be aprupt when the participants move to the other topic or sub topic newly introduced. The relational closeness between topics showed that the topic digressed fastly and there were no return to the previously discussed topics. Topic development in chat might produce linier and parallel sequences. Linier sequences appeared when the participants discuss one topic at one time while parallel sequences appeared when several sub-topic discussed together at the same time. Key words: discourse topic, topic development, chat.